2021
DOI: 10.1007/s11251-021-09547-4
|View full text |Cite
|
Sign up to set email alerts
|

Teaching on video as an instructional strategy to reduce confirmation bias—a pre-registered study

Abstract: The aim of this experiment was to examine the effect of different instructional strategies on student teachers' confirmation bias. Confirmation bias refers to the selectivity in finding and using evidence that fits one's own beliefs or hypotheses while neglecting evidence that is opposite to one's own beliefs or hypotheses (Nickerson, 1998). Dutch student teachers (n = 141) took a confirmation bias pre-test and were then randomly assigned to three conditions; teaching on video (TOV), preparing to teach (PTT) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 72 publications
1
10
0
Order By: Relevance
“…Recently, many researchers found that learners' self-interpretation technique is an effective method to increase GCL. Studies have shown that animations can attract users' attention and motivate them to learn (van Brussel et al, 2021). Researchers proposed that inductive learning strategies and metacognitive monitoring cues can increase learners' GCL and improve their transfer performance.…”
Section: Animation and Cognitive Loadmentioning
confidence: 99%
“…Recently, many researchers found that learners' self-interpretation technique is an effective method to increase GCL. Studies have shown that animations can attract users' attention and motivate them to learn (van Brussel et al, 2021). Researchers proposed that inductive learning strategies and metacognitive monitoring cues can increase learners' GCL and improve their transfer performance.…”
Section: Animation and Cognitive Loadmentioning
confidence: 99%
“…In contrast, teaching expectancy might play an essential role in the benefits of creating videos observed in previous studies ( Hoogerheide et al, 2018 , 2019 ). The studies on teaching by creating videos have shown that students in the teaching on video condition consistently outperform and report more engagement ( Hoogerheide et al, 2016 , 2018 , 2019 ; van Brussel et al, 2021 ). Future work should test whether a teaching expectancy enhances the benefits of creating a video on learning motor skills.…”
Section: Discussionmentioning
confidence: 99%
“…The social presence questionnaire with 10 statements (See Appendix B) was constructed by Van Brussel et al ( 2021 ), and in their study the Cronbach’s alpha was 0.73. In the social presence questionnaire participants had to indicate on a scale from (1) strongly disagree to (5) strongly agree to which degree each of the ten statements represents how they felt after the learning phase.…”
Section: Methodsmentioning
confidence: 99%
“…To measure arousal, the activitation-deactivation adjective check list (ADACL, see Appendix C) by Thayer ( 1967 , 1986 ) was used. This checklist was translated to Dutch and used in a former study by the authors (Van Brussel et al, 2021 ). It assesses core arousal or activation states based on two dimensions (activation and deactivation) and four subscales i.e., energetic, tiredness, tension, and calmness.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation